(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
Process of developing Carnival costumes and/or costumes inside and outside the walls of the classroom and the samba school. Research project developed through many hands and knowledge, from the carnival, passing through research professors, students and alumni, artisan, among other collaborators of this magical party.